Chronological age and biological maturity are separately positively associated with inhibitory control and working memory in boys and girls - Gilbert, Luke M.; Williams, Ryan A.; Morris, John G.; Dunn, Anna; Boat, Ruth; Dring, Karah J.; Nevill, Mary E.; Cooper, Simon B. (Frontiers in Cognition, 2025)
Executive function is typically considered from a chronological age perspective, despite the influence of biological maturity on executive function development. The purpose of this study was to investigate the influence of chronological age and biological maturity on inhibitory control and working memory, separately in boys and girls (due to sex differences in biological maturation). The study employed a cross-sectional design and, following familiarization, 736 (400 female) young people (12.3 ± 1.3 years) completed tests of cognitive function on two separate occasions. Participants completed the Stroop test to measure inhibitory control and the Sternberg paradigm to measure working memory. Chronological age and biological maturity were calculated for each participant. Linear regression models were performed separately for boys and girls. Two models were fit for each test and level of executive function: a chronological age model (executive function x chronological age) and a biological maturity model (executive function x biological maturity). Higher chronological age and biological maturity were associated with superior performance on inhibitory control and working memory tests. In boys, the biological maturity models were a significantly better fit (vs. chronological age), whilst in girls, the chronological age models were a better fit (vs. biological maturity). This study provides novel evidence that biological maturity is associated with inhibitory control and working memory. Emphasizing that future investigations into inhibitory control and working memory in young people should consider biological maturity, especially in boys.